The representation of knowledge in health: Note on controlled vocabularies and ontologies - Souza , Amanda Damasceno de; Filho , Armando Sérgio de Aguiar; Felipe, Eduardo Ribeiro; Farinelli , Fernanda; Almeida , Mauricio Barcellos (Seven Editora, 2023)
It approaches the theme of Knowledge Representation in the health context by describing the informational artifacts necessary for the standardization of languages. Among the artifacts, controlled vocabularies and ontologies are cited, as well as health information sources, due to their importance in supporting health decision-making. Information Science, in its tasks of knowledge organization and representation, contributes information solutions to the Health area. In this context, it becomes necessary for information professionals to know the specificities of language representations in informational artifacts such as controlled vocabularies and ontologies. The controlled vocabulary is used to improve the effectiveness of information storage and retrieval systems, seeking to identify and locate the desired content through standardized language. The ontology represents the knowledge of a domain in individuals, classes, attributes, relations, and events through formal language in its formal relations. In general, the main differences between controlled vocabularies and ontologies refer to their purposes and the way they define their terms. The theoretical notes in this chapter are the result of doctoral research in Information Science. Finally, we emphasize the importance of the work of information professionals in the construction of Knowledge Representation resources, such as controlled vocabularies and ontologies, in domains such as Health, which lack standardized language. DOI:https://doi.org/10.56238/devopinterscie-267